Enhancement of Rectenna Performance Using Artificial Magnetic Conductor for Energy Harvesting Applications - Abu, Maisarah; Jamil Kher, M. S.A; Izahar, Nurul hafiza; A. Latif, A. Fuad; Zabri, S.N. (UTEM, 2015)
This paper brings together an understanding on Artificial Magnetic Conductor (AMC) and rectenna in energy harvesting applications. The rectenna is built upon a combination of a low profile antenna like dipole or patch microstrip with the presence of a rectifying circuit as well as a filter to act as an RF to DC converter. In wireless power transmission, the focal problem is that the total capture of the RF energy is totally low. Thus, with the aim of capturing maximum power, the receiving antenna is supposed to be designed applicably by taking contemplation of several aspects especially the gain. AMC helps to improve the performance of an antenna, hence enhancing the execution of wireless power transmission system of the rectenna. Wireless sensor network is one of the application in wireless power transmission system that applied the approach of energy harvesting, where it is considered to be a practical and deployable solution for today’s technology. Two designs of AMC had been proposed; a rectangular AMC using RO3003 substrate and a square AMC using RO3010 substrate. Simulation results show that the square AMC gives better performance through gain enhancement by 3.529 dB of a half-wave wire dipole antenna with an overall size of 122.45 mm x 122.45 mm.